Studies on genetic variability, correlation coefficient and path analysis in niger (Guizotia abyssinica L. Cass): Studies on genetic variability, correlation coefficient and path analysis in niger (Guizotia abyssinica L. Cass) - S S ATLAWAR; V N TOPROPE; R J SHINDE (Journal of Oilseeds Research, 2020)
Analysis of variances indicated the presence of substantial amount of genetic variability in the genotypes for all the characters. The GCV and PCV were of high magnitude for the character number of capitula/plant followed by number of seeds/capitulum, number of secondary branches/plant and harvest index. The estimate of high heritability coupled with high genetic advance as per cent of mean has been noticed for number of capitulum/plant, number of seeds/capitulum, number of secondary branches/plant, harvest index, number of primary branches/plant, seed yield/plant, oil content and 1000 seed weight indicating the pre dominance of additive gene action in there expressions. Seed yield exhibited positive significant association with 1000 seed weight, number of capitulum/plant, number of seeds/capitulum, number of secondary branches/plant and harvest index.